Upper and Lower Quasi $θτ^\star(σ_1,σ_2)$-continuity (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new concepts of continuous multifunctions, called upper quasi$θτ^\star(σ_1,σ_2)$-continuous multifunctions and lower quasi $θτ^\star(σ_1,σ_2)$-continuous multifunctions. Moreover, several characterizationsand some properties concerning upper quasi $θτ^\star(σ_1,σ_2)$-continuousmultifunctions and lower quasi $θτ^\star(σ_1,σ_2)$-continuous multifunctions are considered.
Keywords: upper quasi $θτ^\star(σ_1,σ_2)$-continuous multifunction; lower quasi $θτ^\star(σ_1,σ_2)$-continuous multifunction